Hagfish to Illuminate the Developmental and Evolutionary Origins of the Vertebrate Retina - Bradshaw, Sarah N.; Allison, W. Ted (Frontiers in Cell and Developmental Biology, 2022)
The vertebrate eye is a vital sensory organ that has long fascinated scientists, but the details of how this organ evolved are still unclear. The vertebrate eye is distinct from the simple photoreceptive organs of other non-vertebrate chordates and there are no clear transitional forms of the eye in the fossil record. To investigate the evolution of the eye we can examine the eyes of the most ancient extant vertebrates, the hagfish and lamprey. These jawless vertebrates are in an ideal phylogenetic position to study the origin of the vertebrate eye but developmental data on eye/retina development in these organisms is limited. New genomic and gene expression data from hagfish and lamprey suggest they have many of the same genes for eye development and retinal neurogenesis as more derived vertebrates, but functional work to determine if these genes operate in retinogenesis similarly to other vertebrates is missing. In addition, hagfish express a marker of proliferative retinal cells (Pax6) near the margin of the retina, and adult retinal growth is apparent in some species. This finding of eye growth late into hagfish ontogeny is unexpected given the degenerate eye phenotype. Further studies dissecting retinal neurogenesis in jawless vertebrates would allow for comparison of the mechanisms of retinal development between cyclostome and gnathostome eyes and provide insight into the evolutionary origins of the vertebrate eye.